Factors associated with modern contraceptive utilization among reproductive age women in Cambodia; evidenced by the recent Cambodia demographic and health survey - Beletu Kinfe; Gosa Mankelkl (Contraception and Reproductive Medicine)
Abstract Introduction Cambodia is a low-income country with limited access to family planning (FP) in terms of modern contraceptive utilization. Despite several FP programs designed to make contraceptives accessible, adoption of contraceptives has been difficult in Cambodia, which has high rates of fertility and maternal mortality. This gap in essential care can put women and adolescent girls at greater risk of adverse outcomes such as stillbirth, spontaneous abortion, unwanted pregnancy, or even maternal death. One of the goals set by the government to decrease both maternal and child mortality and morbidity was increasing the modern contraceptives utilization. So, the main objective of this study was to evaluate spatial variations in modern contraceptives utilization and its contributing factors among women. Methods Data from the Cambodia 2021–22 Demographic and Health Survey datasets were used for secondary data analysis. A total of 19,496 women of reproductive age participated in the study. A spatial and multilevel mixed effects analysis was done on the factors affecting modern contraceptives utilization among Cambodian women. Finally, the percentage, odd ratio, together with their 95% confidence intervals and the results of the spatial analysis were provided. Result The prevalence of modern contraceptive use was 31.2% in Cambodia. Living in an urban area [AOR = 1.224; 95% CI = (1.126.1.330); P = 0.0001]; being married [AOR = 34.131; 95% CI= (12.673, 91.921); P = 0.0001]; and having a history of terminated pregnancy [AOR = 1.137; 95% CI= (1.055, 1.225); P = 0.0001] were found to be positively associated with modern contraceptive utilization. In contrast to this, being between the age range of 46–49 [AOR = 0.421; 95% CI = (0.364, 0.487); P = 0.0001]; being a female-headed household [AOR = 0.784; 95% CI = (0.723, 0.850); P = 0.0001]; and current breast feeding [AOR = 0.84; 95% CI = (0.75, 0.93); P = 0.010] were found to be negatively associated with modern contraceptive utilization. Additionally, the spatial analysis of modern contraceptive utilization showed that a higher proportion was utilized in the southern and southwest regions of Cambodia. Conclusion In this study, living in urban area, being married and having history of terminated pregnancy were found positively associated with modern contraceptive utilization. In contrast to this, being old age, being female headed household and being currently breast-feeding women were found negatively associated with modern contraceptive utilization. In addition to this, there were geographic (spatial) variations in modern contraceptive utilization among Cambodian’s women across the country.